Building systems integration for enhanced environmental performance - Vassigh, Shahin (J. Ross Pub., 2011)
Explores a recent trend in architecture that integrates both design and engineering to develop sustainable buildings. That more inclusive approach, they say, cuts out "substantial inefficiencies" from the design and building process. The book also includes detailed and vivid drawings that well illustrate the concepts discussed in the text.
Keywords: Sustainable architecture.; Buildings -- Environmental engineering.; elektronické knihy; electronic books